Correlation model between PM2.5 and atmospheric variables in the city of Villavicencio - Cuéllar Guarnizo, Jairo Alberto; Isaza Domínguez, Lauren Genith; Hernández Alonso, Eduardo Jesús (Ingeniería Solidaria, 2022)
Introduction: This article is the product of the research "Monitoring and Characterization of air quality in the downtown area of Villavicencio", carried out from 2018 to 2020 in Villavicencio - Colombia. Problem: Air quality directly impacts the health of the people who breathe it. Currently Villavicencio does not have enough monitoring stations, nor are there strategies to improve air quality. Objective: The main objective is to collect and analyse atmospheric and air quality information, to determinate the relationship between atmospheric variables and particulate matter. Methodology: Quantitative and experimental research in stages, a number of samples to be taken were defined and a statistical treatment was carried out. Different instruments were used to collect the variables. Results: The linear model between particulate material and atmospheric variables was obtained. The correlation index of particulate material with atmospheric variables was determined. The results were compared with regulations in Colombia and other countries. Conclusion: The results are within the limit allowed by national regulations. Linear models of the relationship between environmental variables and particulate matter were obtained. Originality: There are few studies related to air quality in the region. With the results, improvement actions can be proposed to local administrations to mitigate the impact on air quality in Villavicencio. Limitations: Sample collection time was limited, the availability of equipment in the institution where the research work originated also affected the scope of the work carried out.